Superior Vena Cava Stenosis - Alexandra Mesquita; Fátima Braga (Sociedade Galega de Medicina Interna, 2017)
In August 2000, a 42 years old female, presented at the emergency department complaining of fever, night sweets and weight loss. Physical examination showed axillar adenopathy of 1cm. Blood tests were normal. Thoracic CT scan showed left pleural effusion and axillary, mediastinal, retroperitoneal and inguinal adenopathies. Biopsy revealed Non Hodgkin Follicular Lymphoma (CD20+). Treatment with cyclophosphamide, doxorubicin and prednisolone (CHOP) was started. CT scan evaluation after 6 cycles showed persistant mediastinic adenopathies. The patient started treatment with radiotherapy to the mediastinal area. In July 2006, a new pleural effusion and adenopathies were detected. The patient started chemotherapy with rituximab, ifosfamide, carboplatin and etoposide (R-ICE) and achieved a complete response. In October 2010, recurrence of the disease was detected. Chemotherapy was restarted and complete response achieved. In January 2014, the patient present with facial edema which worsened in the morning (figure 1 and 2 ). She also referred breast and mammary enlarged veins and dyspnea. PET scan was negative for recurrence of the disease. Brain CT scan was normal. Thyroid function, cortisol and auto-immune antibodies were negative. The patient started treatment with corticotherapy (1mg/kg/day) and hyperbaric oxygen therapy. The symptoms did not disappear. Angio-CT showed superior vena cava stenosis and thrombosis (figure 3). The patient started therapy with enoxaparin and therefore was submitted to dilation of the vena cava stenosis; the symptoms disappeared. Follicular lymphoma represents the second most common Non Hodgkin Lymphoma in adults, accounting for 10-20% of all lymphomas (1). It is considered an indolent disease characterized by a relapsing pattern over years. Superior vena cava (SVC) syndrome refers to a constellation of symptoms produced by the obstruction of blood flow through the SVC, resulting in dyspnea, facial and upper-extremity edema, chest pain and dyspnea. Malignancies represent 60%-85% of the etiologies (2) and lymphoma and lung cancer represent 95% of malignancy-related SVC syndrome. The authors wish to emphasize a late complication due to stenosis of superior vena cava which mimetized a superior vena cava syndrome, although no evidence of disease was found; the symptoms were assumed to be a consequence of fibrosis and stenosis caused by previous radiotherapy; this situation is described as a rare complication in the literature (3). Bibliography 1.Luminari, Stefano et al, Follicular lymphoma - treatment and prognostic factors. Rev Bras Hematol Hemoter. 2012; 34(1): 54-59. 2. Grant S et al, Superior vena cava syndrome as an initial presentation of low-grade follicular lymphoma. J Community Support Oncol. 2014 Nov;12(11):415-7. doi: 10.12788/jcso.0088. 3. Putten Van et al, Superior vena cava obstruction caused by radiation induced venous fibrosis, Thorax 2000;55:245-246 doi:10.1136/thorax.55.3.245.